The little book of economics : how the economy works in the real world - Ip, Greg (Hoboken, N.J. : John Wiley & Sons, 2010)
"One positive side-effect of the recent financial market meltdown that toppled giant, century-old institutions and cost millions their jobs is that it created a strong desire among many Americans to better understand how the U.S. economy functions. In The Little Book of Economics, Greg Ip, one of the country's most recognized and respected economics journalists, walks readers through how the economy really works. Written for the inquisitive layman who doesn't want to plow through academic jargon and Greek letters or pore over charts and tables, The Little Book of Economics offers indispensible insight into how the American economy works - or, doesn't. With engaging and accessible prose, the book: provides a comprehensive understanding of each aspect of our economy from inflation and unemployment to international trade and finance; serves as an insider's guide to the people and institutions that control America's economy such as the Federal Reserve and the federal budget; explains the roots of America's current economic crisis and the risks the country faces in its aftermath, such as stratospheric government debt, while offering advice on overcoming these threats; walks readers through the basic concepts and terminology they need to understand economic news; punctures myths and political spin from both the left and the right with candid and often surprising insight. A must read for anyone who wants a better grasp of the economy without taking a course in economics , The Little Book of Economics is a unique and engaging look at how the economy works in all its wonderful and treacherous ways"--
Includes index.
nif 23/04/13
Loans
Keywords: Economics; Little book - economics; United States